Analisis Faktor Penyebab Penurunan BOR di RSUD Sleman - Anggun Elyana; Feby Erawantini; Suratmi Suratmi (Politeknik Negeri Jember, 2020)
One indicator of the fulfillment of health services to the community, especially in hospitals, was the calculation of the Bed Occupancy Rate (BOR). Factors that caused inefficient BOR need to be analyzed. The impact of a inefficient BOR returning decrease of income economic to the hospital. The purpose of this research is to analyze causative factors of decrease BOR in Regional Public Hospital of Sleman. This research is a qualitative research, with the intention of digging deeper causative factors of decrease BOR. research conducted at Regional Public Hospital of Sleman in February-March 2020 with analyze unit is inpatient care unit at Regional Public Hospital of Sleman. Data collection methods by interview and observation as well data analyze by fishbone diagrams. The results showed that the cause of the decrease in BOR was due to uncertain doctor visit schedules, lack of availability of beds, system errors, lack of reward and punishment, number of competing hospitals and less optimal reporting census monitoring. Suggestions to fix the problems that occur in the process of inpatient services due to a decrease in BOR can be improved Evaluate the SPO of inpatient services, Hold outreach to officers, fix SIMRS, improve the performance of marketing parties to attract patients and provide patients with a complete service and policy development (SK) related to reward and punishment.